The advantages of art therapy with autistic adult populations - Francileudo, Francisco Antonio; Pereira, Pedro Victor de Mendonça Cândido (Kairós: Revista Acadêmica da Prainha, 2021)
The treatment and maintenance of populations on the autism spectrum has been the topic of much debate for several decades. Since no approved medication that addresses the specifics of autism exists, several therapies have been developed to try to enhance the lives of these patients. However, there is a striking difference between the quality of resources for children with autism and those made with adults in mind. Through a comprehensive meta-analysis of literature, online assets, and through a composite case made out of several different sources and references for the sake of accuracy, this article proposes that art therapy, and its unique tools to engage patients in a personal level, is a potentially positive direction for the field to focus on. Regardless, it is imperative to give adult populations with autism quality resources to help navigate life, employment and relationships, since they are not eligible for most child-focused services after a certain age.